Dielectric film with high energy density based on polypropylene/maleic anhydride-grafted polypropylene/boron nitride nanosheet ternary system. (November 2022) - Wang, Ciyao; Xing, Zhaoliang; Yan, Shiyu; Shi, Lirui; Hao, Chuncheng; Lei, Qingquan
Highlights: 1 A 2D nanomaterial (BNNSs) was used to develop large-scale production of high performance dielectrics. 2 PP-g-MAH is a good compatibilizer that can benefit the dispersion of the BNNSs. 3 Polypropylene/maleic anhydride-grafted polypropylene/boron nitride nanosheet ternary system nanocomposites were successfully prepared. 4 The maximal discharge energy density of 4.11 J cm −3 was achieved in 1%-BNNSs/PP/PP-g-MAH nanocomposites. Abstract: With the development of advanced power system, high energy storage polymer film capacitors have attracted more and more attention. Polypropylene (PP) membrane is the most commonly used polymer based membrane, accounting for 70% of the total market share of products. Due to its low dielectric loss, it has a high charge-discharge efficiency (η). However, its inherently low dielectric constant (2.2 at 1 kHz) seriously hinders the increase of energy storage density (1–2 J/cm 3 ). In this study, a ternary PP nanocomposite are prepared by melting blending and die pressing crosslinking, which greatly improved the capacitive properties of PP films. The discharge energy density (Ue ) of PP nanocomposite films increased from 1.63 J/cm 3 to 4.11 J/cm 3 by adding a small amount (1 wt%) of BNNSs into PP matrix. Ue increased significantly (152.1%). By utilizing the special layered structure provided by BNNSs, the energy storage capacity of PP/ PP-g-MAH /BNNSs is significantly improved. Graphical abstract: Image, graphical abstract